2017
DOI: 10.1016/s2214-109x(17)30366-2
|View full text |Cite
|
Sign up to set email alerts
|

Fistula recurrence, pregnancy, and childbirth following successful closure of female genital fistula in Guinea: a longitudinal study

Abstract: Belgian Development Cooperation (DGD), Institute of Tropical Medicine of Antwerp (ITM), and Maferinyah Training and Research Center in Rural Health (Guinea).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
1
20
0
1
Order By: Relevance
“…Interventions addressed components of postsurgical social reintegration and rehabilitation needs demonstrated in the literature through education, counseling, physical rehabilitation, improving economic stability, and incorporating a full continuum of care approach . However, no one program modeled the holistic approach recommended by authors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions addressed components of postsurgical social reintegration and rehabilitation needs demonstrated in the literature through education, counseling, physical rehabilitation, improving economic stability, and incorporating a full continuum of care approach . However, no one program modeled the holistic approach recommended by authors.…”
Section: Discussionmentioning
confidence: 99%
“…They may require further medical care depending on injury severity and surgical outcomes, and medical support for subsequent pregnancies and births. Longitudinal studies from sub‐Saharan Africa have identified concerning adversity following fistula surgery, including fistula recurrence, persistent fistula‐related symptoms, subsequent fertility challenges, and adverse perinatal outcomes . In Guinea, 16% experienced fistula recurrence by 24 months .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may also require further medical care depending on the severity of their injuries and surgical outcomes and require healthcare access for subsequent pregnancies and births. Longitudinal studies from sub-Saharan Africa have identified risks of adverse outcome following fistula surgery, including fistula recurrence, persistent fistula-related symptoms, subsequent fertility challenges and adverse perinatal outcomes 11–13. In Guinea, for example, the cumulative incidence of fistula recurrence was 16% at 24 months13.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies from sub-Saharan Africa have identified risks of adverse outcome following fistula surgery, including fistula recurrence, persistent fistula-related symptoms, subsequent fertility challenges and adverse perinatal outcomes 11–13. In Guinea, for example, the cumulative incidence of fistula recurrence was 16% at 24 months13. In Uganda, by 12 months postsurgery, one-third of women continued to experience urinary incontinence, 17% reported weakness and 9% reported general pain 14.…”
Section: Introductionmentioning
confidence: 99%